2014
DOI: 10.1159/000369827
|View full text |Cite
|
Sign up to set email alerts
|

Altered Inhibitory Function of the E-Type Prostanoid Receptor 4 in Eosinophils and Monocytes from Aspirin-Intolerant Patients

Abstract: Prostaglandin (PG) E2 has been implicated in the pathogenesis of aspirin-exacerbated respiratory disease (AERD). E-type prostanoid (EP) receptor 4 is known to confer inhibitory signals to eosinophils and monocytes, amongst others. In this study, we investigated whether the responsiveness of eosinophils and monocytes to PGE2 and EP4 receptor activation is altered in AERD patients. While the expression of the EP4 receptor in eosinophils was unaltered in AERD patients, inhibition of eosinoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…These effects were reversed by PGE 2 . We observed that the expression of the EP4 receptor in blood eosinophils tended to be reduced in AERD patients, and inhibition of eosinophil chemotaxis by PGE 2 or an EP4 agonist was less pronounced in AERD patients as compared to healthy controls (168). Single nucleotide polymorphisms of the ptger2 and ptger4 were detected in aspirin-intolerant Korean patients, predicting lower EP2 and EP4 receptor expression levels (169, 170).…”
Section: The Prostanoid—eosinophil Axis In Non-allergic Diseasesmentioning
confidence: 85%
“…These effects were reversed by PGE 2 . We observed that the expression of the EP4 receptor in blood eosinophils tended to be reduced in AERD patients, and inhibition of eosinophil chemotaxis by PGE 2 or an EP4 agonist was less pronounced in AERD patients as compared to healthy controls (168). Single nucleotide polymorphisms of the ptger2 and ptger4 were detected in aspirin-intolerant Korean patients, predicting lower EP2 and EP4 receptor expression levels (169, 170).…”
Section: The Prostanoid—eosinophil Axis In Non-allergic Diseasesmentioning
confidence: 85%
“…(Ying et al, 2006) While there was no difference in EP 4 expression on eosinophils between AERD subjects and healthy control, inhibition of eosinophil chemotaxis by PGE 2 or an EP 4 receptor agonist (CAY 10598) was reduced in eosinophils from AERD subjects compared to healthy controls. (Luschnig et al, 2014) The oral PGE 1 analogue, misoprostol, did not protect against NSAID-induced AERD symptoms;(Walters, Simon, Woessner, Wineinger, & White, 2017) however, newer PGE 2 agonists should be examined to evaluate this pathway for treatment of AERD.…”
Section: Individual Pgsmentioning
confidence: 99%